Re-examination and illustration of shells of interspecific hybrid tortoises of Testudo horsfieldii (Gray, 1844) and Testudo h. hermanni (Gmelin, 1789) (Testudines: Testudinidae) from the collection of Walter Kirsche in the Dahme-Heideseen nature park, - Karl, Hans-Volker; Safi, Amtyaz; Paust, Enrico (SPC Journal of Environmental Sciences, 2021)
In this paper, we have re-examined and assessed the only existing shells of two interspecific hybrid tortoises of Testudo horsfieldii and Testudo h. hermanni from the Walter Kirsche collections. It is the first detailed examination and measurements of important preserve shells of hybrid tortoises of Testudo taxa. An overview of the systematic relationship and the literature debate is given. Â Â Â